KETULUSAN MERUPAKAN SEBUAH NILAI MORAL YANG TERABAIKAN - H SUJATI, H SUJATI (Universitas Negeri Yogyakarta, 2003)
The Indonesia nation has been in a very seriously ill condition morally nowdays. This is indicated by the fast growing of corruption, collusion and nepotism. This case describes that it is more difficult to find a honest and sincere person. Sincerely becomes a rare thing even though all religious belief teachs sincerity to their jollowers One of the clarifying jocturs is a syndrome of educational practice ehich applies a variety of uniformity in which the student hint, no chance to propose their expression and to do exploration. That's why it is necessapy to grow freedom to give expression and to make exploration in the education domain to support the development of sincarity.